Learning from Black/African American Participants: Applying the Integrated Behavioral Model to Assess Recruitment Strategies for a Glaucoma Genetic Study. Issue 4 (21st March 2022) - Kikut, Ava; Sanyal, Mohima; Vaughn, Marquis; Ridley-Merriweather, Katherine Ellen; Head, Katharine; Salowe, Rebecca; Lomax-Reese, Sara; Lewis, Monica; Ross, Ahmara G.; Cui, Qi N.; Addis, Victoria; Sankar, Prithvi S.; et al.
ABSTRACT: The underrepresentation of African American (AA) participants in medical research perpetuates racial health disparities in the United States. Open-ended phone interviews were conducted with 50 AA adults from Philadelphia who had previously participated in a genetic study of glaucoma that included complimentary ophthalmic screenings. Recruitment for the genetic study was done in partnership with a Black-owned radio station. Thematic analysis of interview transcripts, guided by the integrated behavior model (IBM), identified self-reported motivations for participating in this care-focused and community-promoted research program. Findings revealed that decisions to enroll were influenced by strong instrumental attitudes regarding learning more about personal health and contributing to future care options for others. Notable normative influences that factored into participants' decisions to enroll in the study included hearing about the study from a respected community media outlet, friends, and family. About one-third of respondents discussed past and current racial discrimination in medical research as an important sociocultural frame within which they thought about participation, suggesting that experiential attitudes play a continuing role in AA's decisions to enroll in medical research studies. Medical researchers seeking to recruit AA participants should collaborate with community partners, combine enrollment opportunities with access to health services, and emphasize the potential for new research to mitigate racial inequalities.